Kualitas Mikrobiologis Se’i yang Dicuring Menggunakan Jus Kulit Buah Naga Merah (Hylocereuspolyrhizus) pada Penyimpanan Suhu Ruang - Theresia Ika Purwantiningsih; Kristoforus W. Kia (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2019)
The skin of red dragon fruit (Hylocereus pilyrhizus) contains antiobacterial properties which can inhibit the growth of microorganisms. With the presence of these antibacterial compounds, dragon fruit skin has the potential to become a natural preservative, to replace the use of chemical preservatives such as nitrite in processing se’i (smoked meat typical of East Nusa Tenggara). The results showed that the dragon fruit peel extract inhibited the growth of pathogenic bacteria such as E. coli ATCC 25922 and S. aureus ATCC 25923. The difference in treatment of pathogen bacteria given significantly affected the inhibitory zone of activity of red dragon fruit skin juice bacteria (P<0.05). The use of dragon fruit skin juice as curing material can inhibit bacterial growth and extend the shelf life until the sixth day at room temperature. It can be concluded that the use of dragon fruit skin juice as curing material can inhibit bacterial growth so that it can extend the shelf life at room temperature.